A study of the stock market dynamics in Malaysia 1990 - 2013 - Kan, Yoke Yue (2014)
This dissertation explores the empirical influence of domestic and foreign factors on equity pricing in Malaysia for the period 1990-2013. In addition, this study reviews and discusses the salient features of major bull and bear markets in Malaysia based on past evidence. This research seeks to determine if the dynamics have changed over time with the period of study spanning across major episodes of crisis such as the Asian Financial Crisis, the Global Financial Crisis and the European Debt crisis. Advanced econometric techniques namely unit root test with structural breaks, multivariate cointegration analysis, error correction model and innovation accounting technique are employed in the analysis. The findings show that share prices and macroeconomic variables (inflation rate, industrial production, money supply and US share price) are cointegrated in Malaysia for the period 1990-2013. In the long-run, consumer price index and US share prices contribute positively to share price movement while industrial production and money supply have a negative relations with KLCI. As for short-run dynamic interaction, Malaysia share prices are not significantly affected by lagged information from macroeconomic variables. Macroeconomic activities have weak explanatory power on stock market movements in short-run. Structural change has occurred after the Asian Financial Crisis. The Malaysian stock market is integrated with global markets of the US, UK, Singapore and Thailand. These stock markets do have a tendency to move together in the long run. The increase in integration after the Asian Financial Crisis is likely due structural change. The high degree of exogeneity prior to the Global Financial Crisis may be a sign of decoupling. Based on stylish facts and historical evidence, the following historical events or global circumstances surround a bullish or bearish market in Malaysia: capital flow, political instability, global and regional development, war, change of ratings, market sentiment and outlook, major government policies announcement and speculative activities on corporate developments.